2017
DOI: 10.5539/ass.v13n4p69
|View full text |Cite
|
Sign up to set email alerts
|

Skills and Knowledge Competency of Technical and Vocational Education and Training Graduate

Abstract: The Education Development Plan of Malaysia (Higher Education) carry the nation's aspiration to empower the technical and vocational education and training (TVET) in Malaysia. The emphasis on the development of high quality TVET graduates demands teachers and instructors of TVET who are highly knowledgeable and skilled. Thus, the emphasis on the quality of TVET teachers' education training of Faculty of Technical and Vocational Education (FTVE), Sultan Idris Education University (UPSI) has become an interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…(2017) [15] reported the differences between genders in terms of students' engagement in social activities. A study carried out by Abdul Razaq et al (2017) [16] on genders among multi-ethnic youths revealed that female youths had a difference perceptions toward soft skills practices.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) [15] reported the differences between genders in terms of students' engagement in social activities. A study carried out by Abdul Razaq et al (2017) [16] on genders among multi-ethnic youths revealed that female youths had a difference perceptions toward soft skills practices.…”
Section: Discussionmentioning
confidence: 99%
“…There are several elements contained within competency that involve the personality, actions, abilities, skills and knowledge of an individual in carrying out specified tasks or work. Apart from that, one can determine a presentation or delivery's effectiveness by way of the presenter's individual competence (Ridzwan, 2017) which is the core of human resource management (Che Ghani, Mohd Zaini & Nur Faeeza, 2018). In the context of education, a teacher's excellent competence will have the impact of student success.…”
Section: Teacher's Competency In Achieving the Malaysian Education Qumentioning
confidence: 99%
“…This gives them the opportunity of getting jobs that match their skills and also make them more competitive in the international labor market [11]. Therefore, the purpose of professional certification is to give recognition to competent Indonesian workers based on competence, professionalism, and competitiveness [12].…”
Section: Introductionmentioning
confidence: 99%